(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic was caused by the rapid worldwide spread of its etiological agent, SARS-CoV-2. The context of the health crisis caused changes in the functionality of various sectors of society, including education. In this perspective, to mitigate the damages of the pandemic in the teaching-learning process, many institutions have adopted emergency remote teaching. However, the lack of access to technology, as well as the psychological disorders caused by the pandemic, are associated with deficiencies in the learning of many students. In addition, teachers and students of the Pedagogical Residence faced the need to adapt their methodology to remote teaching. Thus, the objective was to describe the experiences observed and obtained by students of the Pedagogical Residence, of the Biological Sciences course, at the Federal University of Campina Grande, during the duration of the program in a public school in the city of Cuité - Paraíba - Brazil. The residents, under the supervision of the preceptor teacher, participated in academic activities such as the preparation and execution of classes, moments of discussion and correction of activities on the topics covered in remote classes. In this perspective, it is evident that even with the implementation of the Pedagogical Residency in remote teaching, this program provided the attainment of relevant professional experiences for the teaching practice. In addition, it is deemed necessary to maintain the offers of vacancies and scholarships for this program in higher education institutions, since it significantly contributes to improving the professional quality of teachers in training.